Explaining download patterns in open government data: citizen participation or private enterprise?. (7th August 2019) - Bright, Jonathan; Lee, Sumin; Margetts, Helen; Wang, Ning; Hale, Scott
Open data remains one of the most significant current trends in public administration, with hundreds of projects around the world seeking to open up stores of public sector information for future re-use. However, as open data has grown, a critical literature has also emerged which questions who the true beneficiaries of open data are, as well as highlighting the high costs it places on government. Hence systematic research on the actual outcomes of open data projects is urgently needed. This article seeks to explain the factors which promote greater levels of downloads of open government data. We show that the use of profit making datasets far exceeds those which could be used to enhance government transparency or service delivery. We also show that well updated datasets with high quality metadata are more likely to be downloaded. We conclude by supporting currently developing calls for prioritisation in open government data programmes.